Role of Rural and Urban Land and Building Taxes on Regional Original Revenue of Lumajang - Alvia Nur Utami; Galih Wicaksono (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to determine the role of Rural and Urban Land and Building Tax (PBB-P2) on Regional Original Income (PAD) in Lumajang Regency, through measuring the effectiveness and contribution of PBB-P2 to PAD. This type of research is descriptive quantitative, as well as secondary data obtained from a third party. The object of the research is the target and realization of PBB-P2 and PAD revenue in 2018 to 2020 in Lumajang Regency. Based on the data obtained, it shows that the acceptance of PBB-P2 is in the effective category. Meanwhile, its contribution to PAD is in the very low category. So that after knowing the results of this research, the local government is expected to be able to optimize again the revenue sourced from the Rural and Urban Land and Building Tax.